1939
DOI: 10.2307/4582824
|View full text |Cite
|
Sign up to set email alerts
|

Mouth Lesions Associated with Dietary Deficiencies in Monkeys

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1940
1940
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Herlitz (1938), who investigated the vitamin C saturation of children with and without gingivitis, was unable to find any significant difference between the two groups. Similarly Topping and Fraser (1939) concluded that there was no definite relationship between the commoner mouth lesions and vitamin deficiency. The very fact that deficiencies of so many vitamins have been implicated as a cause of the disease is itself a point which throws doubt on their importance.…”
Section: Discussionmentioning
confidence: 99%
“…Herlitz (1938), who investigated the vitamin C saturation of children with and without gingivitis, was unable to find any significant difference between the two groups. Similarly Topping and Fraser (1939) concluded that there was no definite relationship between the commoner mouth lesions and vitamin deficiency. The very fact that deficiencies of so many vitamins have been implicated as a cause of the disease is itself a point which throws doubt on their importance.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52] Studies in monkeys have demonstrated the synergism between oral microbial flora and malnutrition in the production of necrotizing ulcerative gingivitis. 53 Malnutrition not only affects the structural and functional integrity of the tissues but also determines the character of their responses to pathogenic organisms. Also, the younger the individual, the more profound are the effects of malnutrition on tissue resistance.…”
Section: Malnutritionmentioning
confidence: 99%